The study of love relationship and students' performance in UiTM, Sarawak / Farrah Sofya Mohd Sharbini, Meili Lamat and Nur Aishah Abdul Nasir - Mohd Sharbini, Farrah Sofya; Lamat, Meili; Abdul Nasir, Nur Aishah (2009)
This study was done to observe and analyze the love relationship and students’ performance in UiTM, Sarawak. It also aims to see whether its’ effect the study performance of the student or not. It believes that love also as important as study to the students. Besides, the important is to ensure that student can manage their time between love and study performance. Other than that, we will see the awareness of the students towards their study performance instead of their love relationships. Through this research, we will found out the effects of love relationship towards the study performance of Diploma in Public Administration especially part 6 students of UiTM Sarawak.